2016
DOI: 10.1155/2016/9857201
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Plasticity and Behavior: BDNF-Induced Neuromodulation in Uninjured and Injured Spinal Cord

Abstract: Brain-derived neurotrophic factor (BDNF) is a member of the neurotrophic factor family of signaling molecules. Since its discovery over three decades ago, BDNF has been identified as an important regulator of neuronal development, synaptic transmission, and cellular and synaptic plasticity and has been shown to function in the formation and maintenance of certain forms of memory. Neural plasticity that underlies learning and memory in the hippocampus shares distinct characteristics with spinal cord nociceptive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
98
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(104 citation statements)
references
References 185 publications
(205 reference statements)
2
98
2
2
Order By: Relevance
“…2). BDNF can be released from central presynaptic terminals and may act on pre-and postsynaptic tyrosine kinase (TrkB) receptors to facilitate nociceptive transmission (Garraway and Huie 2016).…”
Section: Significance Of Intraganglionic Cross-talk For Nociceptive Tmentioning
confidence: 99%
“…2). BDNF can be released from central presynaptic terminals and may act on pre-and postsynaptic tyrosine kinase (TrkB) receptors to facilitate nociceptive transmission (Garraway and Huie 2016).…”
Section: Significance Of Intraganglionic Cross-talk For Nociceptive Tmentioning
confidence: 99%
“…Some authors found reversal of allodynia with BDNF treatment [131,132,133], or that pronociceptive effects may only occur in the non-injured state [134]. There is also speculation that BDNF’s contribution to spasticity may only be induced by continuously high levels of this factor, and thus a regulated or transient dosage may solve this potential problem [135].…”
Section: Brain-derived Neurotrophic Factormentioning
confidence: 99%
“…BDNF plays a key role in synaptic plasticity, and its increase may be responsible for some of the analgesic effects seen with AMPAkine treatment in our study. BDNF is also expressed in the spinal dorsal horn, where it can have a pro-nociceptive effect [3537]. It is possible that there is a balance between pro- and anti-nocicpetive effects mediated by BDNF signaling.…”
mentioning
confidence: 99%